The use of a high dose of controlled-release oxycodone in a switch from oral morphine: a case report[Polish version: Zastosowanie wysokiej dawki oksykodonu o kontrolowanym uwalnianiu po zmianie z doustnej morfiny – opis przypadku p... 337 - Leppert, Wojciech; Werner, Sebastian (Contemporary Oncology/Współczesna Onkologia, 2011)
We report a patient with advanced cancer of unknown primary site and severe pain successfully switched from high dose of controlled-release (CR) morphine to CR oxycodone. A 71-year-old man was admitted to home hospice due to cancer dissemination to bones and cervical lymph nodes after palliative radiotherapy. His main complain was severe pain (NRS 6-8) in the cervical and thoracic spine that was non-responsive to tramadol, subsequently changed to transdermal fentanyl and CR morphine with final daily dose of 240 mg (40 mg for breakthrough pain) and constipation. Regular morphine was stopped and CR oxycodone 80 mg twice daily was started, after 6 weeks increased to the dose of 100 mg twice daily achieving satisfactory analgesia (NRS 3-4). No significant adverse effects were present during CR oxycodone therapy. The patient continued his regimen successfully until seizure episode due to brain metastases development and referral to a hospital for further treatment.